Joaquim Aierdi i les «Notícies de València i son Regne» (1661-1679) - Escartí, Vicent Josep (Caplletra. Revista Internacional de Filologia, 2001)
The present article is an attempt at making the recent work by Joaquim Aierdi, the most interesting Valencian chronicler of the second half of the XVII century, better known to a wider public. Information is given about the author and the contents of his work.